Pengaruh Digitalisasi Arsip Dan Kompetensi Arsiparis Terhadap Kinerja Pengelolaan Arsip Dengan Motivasi Kerja Sebagai Variabel Mediasi (Studi pada Dinas PRKP Kabupaten Karawang) - Jusmawati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
Effective records management is an important factor in supporting the performance of government organizations. Technological advancements require government institutions to implement records digitalization supported by competent human resources. This study aims to analyze the influence of records digitalization and archivists’ competence on records management performance, with work motivation as a mediating variable. The research employs a quantitative method with a survey approach. The population of this study consists of archival staff at the PRKP Office of Karawang Regency, using a saturated sampling technique. Data were analyzed using SEM-PLS analysis. The results indicate that records digitalization and archivists’ competence have a positive and significant effect on records management performance, both directly and indirectly through work motivation. This study is expected to serve as a consideration for government institutions in improving the quality of records management.